A Single-Tube Two-Step MIRA-CRISPR/Cas12b Assay for the Rapid Detection of Mpox Virus - Ge Hu; Zhijie Wei; Jinlei Guo; Kangchen Zhao; Qiao Qiao; Xiaojuan Zhu; Tao Wu; Heng Rong; Shuo Ning; Ziyang Hao; Ying Chi; Lunbiao Cui; et al. (Viruses)
Mpox is a zoonotic disease caused by the Mpox virus (MPXV). The rapid and accurate diagnosis of MPXV is essential for the timely and effective prevention, control, and treatment of the disease. In this study, we combined Multienzyme Isothermal Rapid Amplification (MIRA) (at 42 °C) and Clustered Regularly Interspaced Short Palindromic Repeats/CRISPR-associated protein 12b(CRISPR/Cas12b) (at 60 °C) to develop a single-tube two-step assay for rapid MPXV detection, leveraging the distinct physical states of tricosane at these temperatures. MIRA amplification primers and CRISPR/cas12b SgRNA were designed based on the MPXV F3L gene. After screening the primers and sgRNAs, the reaction conditions were optimized, and the performances of the assay were evaluated. The detection limit (LOD) of this single-tube two-step MIRA-CRISPR/Cas12b assay for MPXV is four copies of DNA molecules. No cross-reactivity with other pathogens (herpes simplex virus (HSV), Epstein–Barr virus (EBV), Coxsackievirus A16 (CVA16), Enterovirus A71 (EV-A71), and measles virus (MeV)) was found. The assay also showed good consistency with quantitative real-time PCR (qPCR) (Kappa = 0.9547, p < 0.05, n = 100) in the detection of clinical samples, with a sensitivity of 98.5% and a specificity of 97.0%. The single-tube two-step MIRA-CRISPR/Cas12b assay permits the rapid (within 45 min), sensitive, and specific detection of MPXV. The lack of need for opening the reaction tube eliminates the risk of product contamination.